Minimal residual disease-guided stop and start of venetoclax plus ibrutinib for patients with relapsed or refractory chronic lymphocytic leukaemia (HOVON141/VISION): primary analysis of an open-label, randomised, phase 2 trial. Issue 6 (June 2022) - Kater, Arnon P; Levin, Mark-David; Dubois, Julie; Kersting, Sabina; Enggaard, Lisbeth; Veldhuis, Gerrit J; Mous, Rogier; Mellink, Clemens H M; van der Kevie-Kersemaekers, Anne-Marie F; Dobber, Johan A; Poulsen, Christian B; Frederiksen, Henrik; et al.
Summary: Background: Targeted time-limited treatment options are needed for patients with relapsed or refractory chronic lymphocytic leukaemia. The aim of this study was to investigate the efficacy of minimal residual disease (MRD)-guided, time-limited ibrutinib plus venetoclax treatment in this patient group. Methods: HOVON141/VISION was an open-label, randomised, phase 2 trial conducted in 47 hospitals in Belgium, Denmark, Finland, the Netherlands, Norway, and Sweden. Eligible participants were aged 18 years or older with previously treated chronic lymphocytic leukaemia with or without TP53 aberrations; had not been exposed to Bruton tyrosine-kinase inhibitors or BCL2 inhibitors; had a creatinine clearance rate of 30 mL/min or more; and required treatment according to International Workshop on Chronic Lymphocytic Leukemia 2018 criteria. Participants with undetectable MRD (<10 −4 ; less than one chronic lymphocytic leukaemia cell per 10 000 leukocytes) in peripheral blood and bone marrow after 15 28-day cycles of oral ibrutinib (420 mg once daily) plus oral venetoclax (weekly ramp-up 20 mg, 50 mg, 100 mg, 200 mg, up to 400 mg once daily) were randomly assigned (1:2) to ibrutinib maintenance or treatment cessation. Patients who were MRD positive continued to receive ibrutinib monotherapy. Patients who became MRD (>10 −2 ) during observation reinitiated treatment with ibrutinib plus venetoclax. The primary endpoint was progression-free survival at 12 months after random assignment in the treatment cessation group. Progression-free survival was analysed in the intention-to-treat population. All patients who received at least one dose of study drug were included in the safety assessment. The study is registered at ClinicalTrials.gov, NCT03226301, and is active but not recruiting. Findings: Between July 12, 2017, and Jan 21, 2019, 230 patients were enrolled, 225 of whom were eligible. 188 (84%) of 225 completed treatment with ibrutinib plus venetoclax and were tested for MRD at cycle 15. After cycle 15, 78 (35%) patients had undetectable MRD and 72 (32%) were randomly assigned to a treatment group (24 to ibrutinib maintenance and 48 to treatment cessation). The remaining 153 patients were not randomly assigned and continued with ibrutinib monotherapy. Median follow-up of 208 patients still alive and not lost to follow-up at data cutoff on June 22, 2021, was 34·4 months (IQR 30·6–37·9). Progression-free survival after 12 months in the treatment cessation group was 98% (95% CI 89–100). Infections (in 130 [58%] of 225 patients), neutropenia (in 91 [40%] patients), and gastrointestinal adverse events (in 53 [24%] patients) were the most frequently reported; no new safety signals were detected. Serious adverse events were reported in 46 (40%) of 116 patients who were not randomly assigned and who continued ibrutinib maintenance after cycle 15, eight (33%) of 24 patients in the ibrutinib maintenance group, and four (8%) of 48 patients in the treatment cessation group. One patient who was not randomly assigned had a fatal adverse event (bleeding) deemed possibly related to ibrutinib. Interpretation: These data point to a favourable benefit–risk profile of MRD-guided, time-limited treatment with ibrutinib plus venetoclax for patients with relapsed or refractory chronic lymphocytic leukaemia, suggesting that MRD-guided cessation and reinitiation is feasible in this patient population. Funding: AbbVie and Janssen.